Effectiveness of Cognitive Restructuring Therapy on Bullying Behaviour among Secondary School Students in Kwara State - Yusuf, Jamila; Adegbero, Fadilat Oluwakemi (PEDAGOGIA, 2024)
This study examined the effectiveness of cognitive restructuring therapy in reducing bullying behavior among secondary school students in Kwara State. Employing a quasi-experimental design with pre-test and post-test control groups, the research aimed to evaluate the impact of the intervention. The study involved two schools for the experimental groups and one school for the control group, with data collected using the Bullying Behaviour Scale (BBS). Results revealed no significant differences in pre-test scores between the experimental and control groups, ensuring baseline equivalence. Following the intervention, a significant reduction in bullying behavior was observed in the experimental group, evidenced by a notable difference between their pre-test and post-test scores. Conversely, the control group showed no significant changes in bullying behavior, highlighting the effectiveness of cognitive restructuring therapy. The findings underscore the potential of cognitive restructuring as a targeted intervention for addressing bullying behaviors in schools. Based on the results, the study recommends that educational stakeholders, particularly guidance counselors, incorporate cognitive restructuring techniques into school-based intervention programs to create a safer and more supportive learning environment. These findings contribute to the growing evidence supporting cognitive-behavioral strategies in addressing bullying and fostering positive student interactions.